(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
An experiment was carried out on the effects of periphyton on monoculture of Thai sharputi, Puntius gonionotus at the Department of Fisheries Management, Bangladesh Agricultural University, Mymensingh during 7th August to 8th November. In treatment-1 bamboo poles were used as artificial substrate for periphyton production and in treatment-2 there was no artificial substrate (control). Each of the six ponds was stocked with 150 fingerlings of average size 6.41 cm and 3.60 g. The ponds were fertilized fortnightly with manure (cow dung) at a rate of 10 kg decimal-1, urea 60 g decimal-1 and triple super phosphate 90 g decimal-1. During the experimental period, the ranges of physico-chemical parameters viz. air temperature (31.0-35.50C), water temperature (29-320C), water depth (0.56-0.84 m), transparency (32-63 cm), dissolved oxygen (3.5-7.8 mg L-1), pH (6.8-7.9), total alkalinity (44-92 mg L-1), free CO2 (1.5-4.0 mg L-1), phosphate-phosphorus (0.31-1.07 mg L-1) and nitrate-nitrogen (1.12-2.30 mg L-1) were within the productive range and more or less similar in the ponds under treatments-1 and 2. Among the observed biological parameters, there were 35 genera of phytoplankton composed of five groups and 13 genera of zooplankton composed of four groups in the experimental ponds. Thirty three genera under the groups of Bacillariophyceae, Chlorophyceae, Cyanophyceae and Euglenophyceae formed the periphyton on bamboo poles in the experimental ponds. Net fish production of the ponds with periphyton under treatment-1 was about 1.5 times higher than those of the ponds without periphyton (treatment-2). By analysis of variance, it was found that the net fish production of Thai sharputi under treatment-1 was significantly higher than that under treatment-2 (p< 0.05). Finally, it can be concluded that periphyton is one of the preferable food item of Thai sharputi and it is also suggested that growth and production of Thai sharputi can be increased if arrangement is made for periphyton production. Int. J. Agril. Res. Innov. & Tech. 8 (2): 13-23, December, 2018